2024
DOI: 10.3390/polym16040513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aging on the Physical Properties of Knitted Polymeric Materials

Antonija Petrov,
Ivana Salopek Čubrić,
Goran Čubrić

Abstract: Nowadays, as consumer expectations have increased worldwide, the importance of polymer materials performance has been raised to a new level. Efforts are required to produce a high-quality product that maintains its quality despite aging factors in certain geographical locations. In the experimental part of this study, polyester materials produced from conventional and recycled yarns, further intended for the production of sportswear, were exposed to natural weathering. Before and after the exposure, the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…With this material, the elongation at break in the course direction is 2.5 times higher than in the wale direction. This noted difference is in line with a previous study [24], which has shown that there is a significant difference in elongation at break tests in the directions of the courses and wales of polyester materials. In the case of the material to which elastane has been added, the behavior of the material structure changes so that the differences in the values for the different directions of the material are less pronounced.…”
Section: Results Of Tensile Testingsupporting
confidence: 92%
See 1 more Smart Citation
“…With this material, the elongation at break in the course direction is 2.5 times higher than in the wale direction. This noted difference is in line with a previous study [24], which has shown that there is a significant difference in elongation at break tests in the directions of the courses and wales of polyester materials. In the case of the material to which elastane has been added, the behavior of the material structure changes so that the differences in the values for the different directions of the material are less pronounced.…”
Section: Results Of Tensile Testingsupporting
confidence: 92%
“…While interest in sports-related materials is increasing, the literature review pointed out that specific aging protocols for functional sportswear are lacking. Previous studies have shown that aging has an effect on certain physical–mechanical characteristics, but it is concluded that these changes should not significantly affect the athlete’s performance [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%